2016
DOI: 10.3892/mmr.2016.6098
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol inhibits adventitial fibroblast proliferation and induces cell apoptosis through the SIRT1 pathway

Abstract: Atherosclerosis is one of the most important causes of cardiovascular disease and studies have showed that adventitial fibroblasts, which are considered to be the most common cell type of the vascular adventitia, are involved in the development of early atherosclerotic plaques. Resveratrol is a plant polyphenolic compound confirmed to have anti-atherosclerotic and cardioprotective effects. The aim of the present study was to investigate the effects of resveratrol on adventitial fibroblasts in vitro and to clar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…The atheroprotective effect of SIRT1 is also exerted through the fine modulation of EPC senescence and adventitial fibroblast migration (107,124). In particular, in EPCs, the nicotinamide phosphoribosyltransferase (NAMPT), the rate-limiting enzyme in the NAD + biosynthetic pathway, attenuates oxLDL-induced senescence by upregulating SIRT1 expression through the PI3K/Akt/ERK pathway (124).…”
Section: Sirt1 and Atherosclerosismentioning
confidence: 99%
“…The atheroprotective effect of SIRT1 is also exerted through the fine modulation of EPC senescence and adventitial fibroblast migration (107,124). In particular, in EPCs, the nicotinamide phosphoribosyltransferase (NAMPT), the rate-limiting enzyme in the NAD + biosynthetic pathway, attenuates oxLDL-induced senescence by upregulating SIRT1 expression through the PI3K/Akt/ERK pathway (124).…”
Section: Sirt1 and Atherosclerosismentioning
confidence: 99%
“…Among SIRT family, SIRT1 has been validated to be most related in this family and function as deacetylating and regulating histones (Ling et al, 2018) as well as a wide range of non-histone substrates, such as NF-κB (Kauppinen et al, 2013), p53 (Nakamura et al, 2017), FOXO (Brunet et al, 2004), ERK (Han et al, 2017), peroxisome proliferator-activated receptor γ (PPARγ) and others (Kauppinen et al, 2013). With regulating this protein, SIRT1 plays a central role in regulating cellular processes, including apoptosis (Ling et al, 2017), cellular proliferation (Jablonska et al, 2016), and inflammation . In the nervous system, SIRT1 suppress the neurodegenerative diseases such as Alzheimer's disease and Parkinson's disease via anti-apoptosis, anti-inflammation (Singh et al, 2017;Gomes et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It can inhibit the proliferation of pathological scar fibroblasts via downregulating the expression of mammalian target of rapamycin (mTOR) /70S6K signaling pathway or TGF-β1, Smad-2, 3,4, and upregulating expression of Smad 7 [58,59]. It can also inhibited proliferation of hypertrophic scar-derived fibroblasts and adventitial fibroblast in vitro and led to a more organized and thinner collagen fibre in the mouse model of wound healing via up-regulating expression of Sirt1 [60][61][62]. Here, we showed that resveratrol could enhance viability of NIH3T3 cells via activating the Shh signaling pathway.…”
Section: Discussionmentioning
confidence: 99%